BOARD CHARACTERISTICS AND CSR DISCLOSURE ON SOCIAL MEDIA X: (EVIDENCE FROM INDONESIAN LISTED COMPANIES) - Hidayah, Tasya Ainun; Suryani, Ani wilujeng (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: CSR disclosures often emphasize social and environmental achievements while ignoring negative aspects that harm the environment, which can lead to public skepticism. Companies can utilize CSR disclosures on social media to increase trust in sustainability claims. This study aims to determine the effect of board characteristics, namely board independence, female directors, and board education level, on CSR disclosure on social media X.Methods: This study employs multiple regression analysis grounded in stakeholder theory, using 5,852 tweets from X (Twitter) accounts of companies in the basic materials, industrials, consumer non-cyclicals, consumer cyclicals, healthcare, and technology sectors listed on the Indonesia Stock Exchange in 2023. This study analyzes CSR disclosure on social media X as the dependent variable with board independence, the presence of female directors, and the education level of the board of directors as independent variables.Results: The multiple regression results show that the education level of the board of directors has a positive effect on CSR disclosure on social media. However, board independence and female directors have no effect on CSR disclosure on social media. Conclusion and suggestion: These findings highlight the importance of the individual qualities of the board of directors in encouraging CSR transparency through social media. Companies should give greater consideration to the educational background of board members, as boards with higher educational attainment are more likely to recognize the importance of information disclosure and the strategic use of social media for stakeholder communication. Keywords: Board of Education, Board of Directors, Corporate Social Responsibility, CSR Disclosure, Social Media,